2010
DOI: 10.1128/aem.01535-10
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Non-Superoxide Anion Reactive Oxygen Species Mediates Nitrogen-Limited Alcoholic Fermentation by Saccharomyces cerevisiae

Abstract: Throughout alcoholic fermentation, nitrogen depletion is one of the most important environmental stresses that can negatively affect the yeast metabolic activity and ultimately leads to fermentation arrest. Thus, the identification of the underlying effects and biomarkers of nitrogen limitation is valuable for controlling, and therefore optimizing, alcoholic fermentation. In this study, reactive oxygen species (ROS), plasma membrane integrity, and cell cycle were evaluated in a wine strain of Saccharomyces cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…For example, autophagy induction is observed during the primary fermentation of synthetic grape must, 867 and during sparkling wine production (secondary fermentation). 868 A number of genome-wide studies have identified vacuolar functions and autophagy as relevant processes during primary wine fermentation or for ethanol tolerance, based on gene expression data or cell viability of knockout yeast strains; 867,[869][870][871][872][873] however, understanding the actual relevance of autophagy in yeast-driven food fermentation processes would require addressing this issue experimentally using some of the methods available for S. cerevisiae as described in these guidelines.…”
Section: Do Not Distributementioning
confidence: 99%
“…For example, autophagy induction is observed during the primary fermentation of synthetic grape must, 867 and during sparkling wine production (secondary fermentation). 868 A number of genome-wide studies have identified vacuolar functions and autophagy as relevant processes during primary wine fermentation or for ethanol tolerance, based on gene expression data or cell viability of knockout yeast strains; 867,[869][870][871][872][873] however, understanding the actual relevance of autophagy in yeast-driven food fermentation processes would require addressing this issue experimentally using some of the methods available for S. cerevisiae as described in these guidelines.…”
Section: Do Not Distributementioning
confidence: 99%
“…This dye does not fluoresce in the reduced form, but when it enters an actively respiring cell, it is oxidized by ROS in the mitochondria to form a red fluorescent compound (32,37). Yeast cells, obtained as described above, were resuspended in 2 ml PBS containing 40 g ml Ϫ1 of the dye prepared in dimethyl sulfoxide (Ն99.9%; Sigma) and incubated for 15 min at 26°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…The red fluorescence of PI or MitoTracker Red was detected on an FL3 log filter through a 590-nm long pass, a 620-nm band pass, and another 670-nm long pass. An acquisition protocol was defined to measure forward scatter (FS log), side scatter (SS log), and red fluorescence (FL3 log) on a 4-decade logarithmic scale (32,37). Each replicate was sampled three times, and 25,000 cells per sample were scanned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations